2022
DOI: 10.1186/s12974-022-02495-x
|View full text |Cite
|
Sign up to set email alerts
|

DKK3 ameliorates neuropathic pain via inhibiting ASK-1/JNK/p-38-mediated microglia polarization and neuroinflammation

Abstract: Background Neuropathic pain is a common and severely disabling state that affects millions of people worldwide. Microglial activation in the spinal cord plays a critical role in the pathogenesis of neuropathic pain. However, the mechanisms underlying spinal microglial activation during neuropathic pain remain incompletely understood. Here, we investigated the role of Dickkopf (DKK) 3 and its interplay with microglial activation in the spinal cord in neuropathic pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The concentrations of IL-1β, IL-6 and TNF-α in the collected DRG samples were measured using rat IL-1β (ER9074, Wellbi Biological Technology, China) TNF-α (ER9113M, Wellbi Biological Technology, China) and IL-6 (ER9078M, Wellbi Biological Technology, China) ELISA kits [ 30 ]. In brief, six diluted standard protein (720, 360, 180, 90, 45, and 22.5 µg/L) in 50 µL buffer and 50 µL of blank control buffer were added into the 96-well plate in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of IL-1β, IL-6 and TNF-α in the collected DRG samples were measured using rat IL-1β (ER9074, Wellbi Biological Technology, China) TNF-α (ER9113M, Wellbi Biological Technology, China) and IL-6 (ER9078M, Wellbi Biological Technology, China) ELISA kits [ 30 ]. In brief, six diluted standard protein (720, 360, 180, 90, 45, and 22.5 µg/L) in 50 µL buffer and 50 µL of blank control buffer were added into the 96-well plate in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…A number of previous studies have shown that activation of the JNK/p‐38 pathway is important for the polarization of microglia in inflammatory settings. Zhang et al (2022) revealed that Dickkopf 3 ameliorates neuropathic pain by inhibiting JNK/p‐38‐mediated microglial polarization and neuroinflammation. Ye et al (2021) demonstrated that quercetin alleviates chronic constriction injury‐induced neuralgia in rats by activating the JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that 7 days after SNI, the microglia in the spinal dorsal horn were significantly reactive, which manifests as increased numbers, larger cell bodies, and shorter branches. After SNI, microglia can be overactive through the ASK-1/JNK/P-38 pathway and tend toward a harmful stage ( Zhang et al, 2022 ). To investigate the alteration of microglia during NP development, the characteristics of microglia in the spinal dorsal horn were observed on days 3, 7, and 14 of SNI rats.…”
Section: Discussionmentioning
confidence: 99%